Intermediate-Term Results of Extracorporeal Membrane Oxygenation Support Following Congenital Heart Surgery. (April 2014) - Peer, Syed M.; Emerson, Dominic A.; Costello, John P.; Shu, Michael K.; Zurakowski, David; Jonas, Richard A.; Berger, John T.; Nath, Dilip S.
Background: Although there are considerable data regarding in-hospital results of congenital heart surgery (CHS) patients requiring postoperative extracorporeal membrane oxygenation (ECMO) support, there is limited information on intermediate-term outcomes. Methods: A single-institution retrospective review of 25 consecutive postoperative CHS patients who required ECMO and survived to hospital discharge between January 2003 and June 2008. Survival was estimated by the Kaplan-Meier method. Results: At a median follow-up of 3.3 years (interquartile range: 1.2-5.9 years), there was one death which occurred at six months postsurgery. Kaplan-Meier-estimated survival at three years was 95% (95% confidence interval: 90%-100%). Indications for ECMO included extracorporeal cardiopulmonary resuscitation (48%), systemic hypoxia (4%), postoperative low-cardiac output syndrome (28%), and intraoperative failure to wean off cardiopulmonary bypass (20%). Following ECMO support, 65% of patients had unplanned cardiac reinterventions (three requiring operative interventions, six requiring percutaneous interventions, and four requiring both), and 47% of patients required unplanned hospitalizations. In all, 29% of patients developed neurological deficits and 12% of patients developed chronic respiratory failure. No patients developed renal failure. Overall, systemic ventricular (SV) function normalized in 83% of patients, whereas 17% of patients had persistent mild-to-moderate SV dysfunction. Conclusions: Intermediate-term patient survival of ECMO following CHS is encouraging. However, neurological impairment and unplanned cardiac reinterventions remain significant concerns. Further delineation of risk factors to improve patient outcomes is warranted.